OPTIMAL LEARNING USING TECHNOLOGY: AMPLIFYING STUDENTS COLLABORATION AND SOCIAL NETWORKING - Pearce, Angela (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Technology for learning has great potential in enhancing social networking and collaboration opportunities among students. Implementing technology into learning environments has been known to increase students’ academic experiences and learning outcomes. However, evidence remains unclear when it comes to showing that students have learned while using technology. Learning with technology can increase personal well-being. The Well-being Theory and PERMA model will be used as the theoretical framework to show how optimal learning with technology can improve students' outcomes and contribute to multidimensional well-being components. This is not only true for young students, as older individuals’ partake in academia and use technology to increase their learning experiences. The research was based on previous literature on learning with technology and how to enhance personal well-being. Findings revealed that learning with technology does strengthen teaching and learning experiences. It also contributes to positive attitudes toward learning with technology when students and teachers are provided with adequate training. It will provide information related to how learning with technology influences collaboration and fosters social networking. Finally, the conclusion will be based on the rationale for using technology for learning and its contribution to personal well-being. Future research recommendations and limitations are addressed.